2018
DOI: 10.1002/acn3.671
|View full text |Cite
|
Sign up to set email alerts
|

Pilot trial of inosine to elevate urate levels in amyotrophic lateral sclerosis

Abstract: ObjectiveTo test the safety, tolerability, and urate‐elevating capability of the urate precursor inosine taken orally or by feeding tube in people with amyotrophic lateral sclerosis (ALS).MethodsThis was a pilot, open‐label trial in 25 participants with ALS. Treatment duration was 12 weeks. The dose of inosine was titrated at pre‐specified time points to elevate serum urate levels to 7–8 mg/dL. Primary outcomes were safety (as assessed by the occurrence of adverse events [AEs]) and tolerability (defined as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 54 publications
0
43
0
1
Order By: Relevance
“…Real‐time motion correction with shim update has been used in clinical MRSI studies with adult subjects, including clinical studies of patients with brain tumors, 91 amyotrophic lateral sclerosis (ClinicalTrials.gov/NCT02288091), 92 multiple sclerosis, and neurodegenerative disorders (eg Parkinson's disease and mild cognitive impairment) 93 . Cancer IDH mutations (IDH 1&2) have high de novo production of the oncometabolite 2HG, and in vivo imaging of 2HG is a key application of MRSI in neuro‐oncology.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Real‐time motion correction with shim update has been used in clinical MRSI studies with adult subjects, including clinical studies of patients with brain tumors, 91 amyotrophic lateral sclerosis (ClinicalTrials.gov/NCT02288091), 92 multiple sclerosis, and neurodegenerative disorders (eg Parkinson's disease and mild cognitive impairment) 93 . Cancer IDH mutations (IDH 1&2) have high de novo production of the oncometabolite 2HG, and in vivo imaging of 2HG is a key application of MRSI in neuro‐oncology.…”
Section: Applicationsmentioning
confidence: 99%
“…Robust 3D MRSI of 2HG with real‐time ReShMoCo MEGA editing was used in mutant IDH glioma patients to assess tumor burden, 94 response to standard radiochemotherapy, 91 and targeted therapy with novel mutant‐IDH inhibitors. 91,95 The same methodology was used to image GSH in the brains of patients with amyotrophic lateral sclerosis (ClinicalTrials.gov/NCT02288091), 92 including the motor cortex and corticospinal tracts, or in patients with mutant IDH glioma tumors 95 . GABA was imaged using the same methods in patients with Parkinson's disease 93 .…”
Section: Applicationsmentioning
confidence: 99%
“…Oral administration of inosine has been explored in clinical trials to treat neurological conditions such as Parkinson’s disease (PD). Inosine administration elevates the urate levels in serum and cerebrospinal fluid (CSF), thus affording neuroprotection through radical scavenging [ 53 , 54 , 55 ]. In PD patients, inosine administration may slow the progression of mental disability, but a phase 3 trial was prematurely terminated as the anticipated efficacy was not met [ 56 ].…”
Section: Molecular Inosine In Metabolism and Signalingmentioning
confidence: 99%
“…This was highlighted in different experimental studies in vitro but positive outcomes have also emerged in PD mouse models, encouraging scientists to consider preclinical studies also on ALS models [172,173]. Nowadays, there are some clinical trials that have confirmed safety and efficacy of inosine in increasing urate levels in both pathologies (NCT00833690; [174]; NCT02288091; [175]).…”
Section: Synthetic Antioxidantsmentioning
confidence: 99%